Effects of graphite content on the microstructure and wear properties of an AISI 8620 steel surface modified by tungsten inert gas (TIC) - Celik, Osman Nuri; Ulutan, Mustafa; Gasan, Hakan; Er, Umit; Buytoz, Soner (Elsevier Science Sa, 2011)
A surface modification process was used to modify the surface properties of a steel material by using the TIC method on AISI 8620 steel with a 135-A constant energy input and the addition of 0.5 g of constant SIC particle and variable C content. SEM and optical microscopy were used to characterize the microstructure of the materials tested. To evaluate the mechanical properties, the microhardness distribution was determined from the surface to the central region. Wear tests were performed under dry friction conditions with WC balls at a 5-N normal load in a ball-on-disk geometry. The results of this study indicated that the surface properties of the material could be modified with the TIG method and by using SiC/C particles and that the newly formed structure could improve the wear characteristics and the hardness of the surface. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TIC surface modification; Friction; Wear; SiC/C diffusion